Payment preferences of hawkers in Singapore : a discrete choice experiment - Yeo, Elizabeth Pei Yee (Nanyang Technological University, 2021)
In this study, we aim to identify the underlying factors that affects the slow adoption of mobile payment in hawkers as compared to other industries. Using a discrete choice experiment to elicit willingness to pay, this study examined hawkers’ preference in payment methods by measuring the two main attributes – usage of smartphone and risk of fraud. Individual characteristics, business characteristics and knowledge, attitude, and practice (KAP) questions were also interacted with the main attributes to explore their impact on utility. Our results show that stallholders exhibit disutility and must be compensated $72.51 to use smartphone in their business operations. The main deterrent for adoption of mobile payment is the exposure to possibility of fraud. Stallholders have a linear WTP function with respect to the probability of fraud and must be compensated $149.24 for 3% risk of fraud relative to 2%. There is also a significant relationship between the location of the stall as well as stallholder’s preference of mobile payment. These results have important policy implications and will provide policymakers a holistic view of the general acceptance of mobile payment in the hawker business.